Labour law and sustainable development - Cagnin, Valentina (Studies in employment and social policy ;, 2020)
It is no exaggeration to assert that the existing foundations of labour law have been irreversibly compromised. It is essential to find a way out of the crisis, at the same time defining the founding values of a new sustainable labour law. In linking labour law with the sustainability paradigm, this provocative book promises to widen the scope and terms of the reconciliation of interests, fully taking into account the multiplicity of the stakeholders interested in economic, social and environmental issues and in particular to practise an approach that achieves intergenerational equity.